2018
DOI: 10.1016/j.apcatb.2018.04.023
|View full text |Cite
|
Sign up to set email alerts
|

On the soot combustion mechanism using 3DOM ceria catalysts

Abstract: Vicente s/n. E03080, Alicante (Spain). HIGHLIGHTS  Ceria catalysts have been prepared with conventional (Ref) and three dimensionally order macroporous (3DOM) structures  3DOM ceria is more active for soot combustion than conventional Ref ceria  3DOM ceria produces more active oxygen than conventional Ref ceria  3DOM ceria catalysts transfer active oxygen to soot more efficiently than conventional Ref ceria  3DOM ceria catalysts utilizes NO2 more efficiently than conventional counterpart Ref ceria

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(50 citation statements)
references
References 40 publications
1
49
0
Order By: Relevance
“…NO 2 -assisted soot combustion over three dimensionally ordered macroporous (3DOM) ceria-based catalysts was studied in [ 83 ]. Both the use of the colloidal crystal template of monodisperse spheres of PMMA and the addition of copper via impregnation step contributed to the high efficiency of the catalyst.…”
Section: Ceria Preparation Methods Based On Artificial Templatesmentioning
confidence: 99%
“…NO 2 -assisted soot combustion over three dimensionally ordered macroporous (3DOM) ceria-based catalysts was studied in [ 83 ]. Both the use of the colloidal crystal template of monodisperse spheres of PMMA and the addition of copper via impregnation step contributed to the high efficiency of the catalyst.…”
Section: Ceria Preparation Methods Based On Artificial Templatesmentioning
confidence: 99%
“…PMMA colloidal crystals were prepared following the methodology previously described elsewhere. [23,24] After synthesis, a cerium citrate ethanolic solution was infiltrated into the PMMA colloidal crystals. This cerium citrate solution (0.476 M) was obtained by dissolving cerium nitrate (Ce(NO 3 ) 3 · 6H 2 O) and citric acid in stoichiometric proportion in ethanol.…”
Section: Methodsmentioning
confidence: 99%
“…Considering the same concept, three-dimensionally ordered macroporous (3DOM) catalysts have demonstrated an improved activity in soot combustion in comparison to their disordered equivalent, which was associated to the enhanced soot-catalyst contact. [23][24][25] However, this porosity is not optimized to the soot morphology and only several contact points are still achieved. 3DOM structures are composed by spherical voids typically with 50-300 nm of diameter [26][27][28][29] whereas soot particles are formed by agglomerated spherical primary particles with an average primary particles diameter ranging from 10 to 25 nm and average aggregate sizes in the range of 50 to 300 nm.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of VOCs, and particularly in the case of the oxidation of the remaining hydrocarbons (HC), the following oxidic systems and compounds have been reported as being active: Co 3 O 4 , MnO 2 , CeO 2 , and CuO [21][22][23][24][25][26][27][28][29][30][31]. The combustion reaction of particulate matter has been extensively studied in recent decades, identifying catalysts with very diverse active phases [32][33][34][35][36][37][38][39][40][41]. A meticulous study of them can be found in a review by A. Bueno Lopez et al [32] and in a more recent review by D. Fino et al [33].…”
Section: Introductionmentioning
confidence: 99%